Implementation of the Basel Core Principles for Effective Banking Supervision : Experience with Assessments and Implications for Future Work. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper reviews the experience to date in assessing countries' compliance with the Basel Core Principles for Effective Banking Supervision (BCP). This review is based on 136 assessments conducted under the FSAP/OFC programs, using the methodology associated with the 1997 version of the BCP. It follows earlier reviews presented to the Board in 2000, 2002, and 2004. The Fund has developed a strong collaborative relationship with the Basel Committee in promoting financial stability, in particular, in its work through the FSAP program in assessing (together with the Word Bank) the quality of countries' supervisory structures. Experience gained from these assessments are also being reported back to the Committee through the Fund's participation in Basel working groups, and staff has also been actively involved in the update of the BCP in 2006, with the objective of maintaining the BCP's relevance as a global standard of good practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet